Development of an intelligent system for tracking RFID tags applied to Industry 4.0 - Serrão, Alacy da Conceição da Silva (2024)
The market for traceability systems for software projects is expanding rapidly, driven by the growing demand for efficient monitoring and control solutions. Companies from various sectors are looking to these systems to guarantee transparency and security in their operations. Technological innovations and advanced integrations are shaping this market, making it highly competitive. In view of this market vision, this research aims to develop a software project to meet the requirements of inventory processes and logistics 4.0, applied to the business rules of a company in the Manaus industrial estate in the adhesive tape business. The research focuses on software computing and its development methodologies. To achieve this, it was necessary to specify and catalogue the technical requirements (functional and non-functional) of software development and traceability processes. This made it possible to model and prototype the system that precedes data acquisition. In addition, Design Patterns were applied to the programming stacks to facilitate the integration of the computer models. These models are responsible for acting as Business Intelligence (BI) for agents external to the system, generating stock indicators and business rules. Development included carrying out and reporting on test scenarios with computer simulation, focusing on the needs and requirements of quality and synchronisation. This process ensured that the system was able to monitor the behaviour of devices, data, functionalities, response delivery, bottlenecks, unforeseen technical impediments, server performance, service performance (API), interface performance (frontend) and dashboard projections. Extreme Programming (XP) and Kanban methodologies were used to achieve these objectives. Trello was used to control activities. The application of these methodologies, together with modern programming stacks, resulted in a robust and satisfactory system. Computational optimisation techniques, antenna triangulation and functional and stress tests of the RFID equipment were implemented for future improvements. In summary, the research has developed an efficient and effective traceability system, adapted to the specific needs of the adhesive tape sector in the Manaus industrial estate. The use of agile methodologies and modern tools ensured a high-quality end product, ready to meet the demands of inventory monitoring and control and logistics 4.0. The technological innovations incorporated and the robustness of the system position the company competitively in the market, providing transparency, security and operational efficiency.